2022
DOI: 10.1097/ta.0000000000003650
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative endovascular balloon occlusion of the aorta for life-threatening postpartum hemorrhage: A nationwide observational study in Japan

Abstract: BACKGROUND:Resuscitative endovascular balloon occlusion of the aorta (REBOA) is used for postpartum hemorrhage (PPH), which is one of the leading causes of maternal mortality worldwide; however, its utility in the obstetrics setting remains unclear. Thus, this study aimed to describe the characteristics, demographics, and mortality of patients with PPH who underwent REBOA. METHODS:We used the Japanese Diagnosis Procedure Combination inpatient database to identify patients with PPH who underwent REBOA from Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In addition, REBOA is increasingly used for placenta accreta spectrum disorders, 10 which also includes our institution. Recently a large observational study from Japan was published, 11 in addition to several previous case reports. 12,13 In 2017, Nyfløt et al observed that the frequency of severe PPH (defined as blood loss ≥1500 mL) was 2.5% in three Norwegian University Hospitals, 14 the most common etiologies were uterine atony (60%) and placental complications (36%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, REBOA is increasingly used for placenta accreta spectrum disorders, 10 which also includes our institution. Recently a large observational study from Japan was published, 11 in addition to several previous case reports. 12,13 In 2017, Nyfløt et al observed that the frequency of severe PPH (defined as blood loss ≥1500 mL) was 2.5% in three Norwegian University Hospitals, 14 the most common etiologies were uterine atony (60%) and placental complications (36%).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, REBOA is increasingly used for placenta accreta spectrum disorders, 10 which also includes our institution. Recently a large observational study from Japan was published, 11 in addition to several previous case reports. 12 , 13 In 2017, Nyfløt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although the concept can be traced back to the Korean war [3], this specific technique reemerged and became popular in the past two decades [4,5]. Despite the questionable survival benefits, REBOA is currently being used not only for trauma, but also for other causes of abdominal bleeding, such as ruptured aortic aneurysm, post-partum hemorrhage, and gastrointestinal bleeding [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…4,9 Catheter-based aortic occlusion has also been successfully applied to nontraumatic hemorrhage. [10][11][12] Although these results are encouraging, the exact role of REBOA within a trauma algorithm remains undefined, and current guidelines only recommend its use in hemodynamically unstable patients with pelvic injuries. 13 Likewise, the role of REBOA in traumatic cardiac arrest remains undefined.…”
mentioning
confidence: 99%
“…Observational studies of REBOA have shown associations with improved survival in patients with traumatic hemorrhage, particularly those with pelvic hemorrhage, although these benefits are not demonstrated consistently, and there are no randomized controlled trials to inform its use 4,9 . Catheter-based aortic occlusion has also been successfully applied to nontraumatic hemorrhage 10–12 . Although these results are encouraging, the exact role of REBOA within a trauma algorithm remains undefined, and current guidelines only recommend its use in hemodynamically unstable patients with pelvic injuries 13 …”
mentioning
confidence: 99%